Comprehensive analysis of the endoplasmic reticulum stress response in the soybean genome: conserved and plant-specific features. (December 2015) - Silva, Priscila; Silva, José; Caetano, Hanna; Machado, Joao; Mendes, Giselle; Reis, Pedro; Brustolini, Otavio; Dal-Bianco, Maximiller; Fontes, Elizabeth
Abstract Background Despite the relevance of the eukaryotic endoplasmic reticulum (ER)-stress response as an integrator of multiple stress signals into an adaptive response, knowledge about these ER-mediated cytoprotective pathways in soybean (Glycine max) is lacking. Here, we searched for genes involved in the highly conserved unfolded protein response (UPR) and ER stress-induced plant-specific cell death signaling pathways in the soybean genome. Methods Previously characterized Arabidopsis UPR genes were used as prototypes for the identification of the soybean orthologs and thein silico assembly of the UPR in soybean, using eggNOG v4.0 software. Functional studies were also conducted by analyzing the transcriptional activity of soybean UPR transducers. Results As a result of this search, we have provided a complete profile of soybean UPR genes with significant predicted protein similarities toA. thaliana UPR-associated proteins. Both arms of the plant UPR were further examined functionally, and evidence is presented that the soybean counterparts are true orthologs of previously characterized UPR transducers in Arabidopsis. The bZIP17/bZI28 orthologs (GmbZIP37 and GmbZIP38) and ZIP60 ortholog (GmbZIP68) from soybean have similar structural organizations as their Arabidopsis counterparts, were induced by ER stress and activated an ERSE- and UPRE-containing BiP promoter. Furthermore, the transcript of the putative substrate of GmIREs, GmbZIP68, harbors a canonical site for IRE1 endonuclease activity and was efficiently spliced under ER stress conditions. In a reverse approach, we also examined the Arabidopsis genome for components of a previously characterized ER stress-induced cell death signaling response in soybean. With the exception of GmERD15, which apparently does not possess an Arabidopsis ortholog, the Arabidopsis genome harbors conserved GmNRP, GmNAC81, GmNAC30 and GmVPE sequences that share significant structural and sequence similarities with their soybean counterparts. These results suggest that the NRP/GmNAC81 + GmNAC30/VPE regulatory circuit may transduce cell death signals in plant species other than soybean. Conclusions Ourin silico analyses, along with current and previous functional data, permitted generation of a comprehensive overview of the ER stress response in soybean as a framework for functional prediction of ER stress signaling components and their possible connections with multiple stress responses.